HUBUNGAN INDEKS MASSA TUBUH YANG TINGGI (OBESITAS) DENGAN KEJADIAN FLAT FEET PADA MAHASISWA FAKULTAS KEDOKTERAN UPN VETERAN JAKARTA TAHUN AJARAN 2019/2020 - Shifa Azzahra (2020)
Flat feet is a condition characterized by flattening arch of the foot (medial longitudinal arcus) while supporting the body weight. The prevalence of flat feet is still not clearly known yet, because there is no clinical consensus or radiological criteria to determine flat feet. One factor that might cause a flat feet is obesity. An obese person will put a higher pressure on the arch of the foot compared with others that have a normal body mass index, so it will cause a flattening on arch of the foot. Medical Faculty students have high risk of obesity due to lack of physical activity and irregular eating pattern. The purpose of this study was to determine the relation of high body mass index (obesity) and the incidence of flat feet in Medical Faculty of UPN Veteran Jakarta students . This methodological research used cross sectional design with 99 students as subject. Foot arcs were assessed by a foot print test and BMI were calculated after measurement height and weight of subject. The results of this study indicated that there is a significant relation between body mass index and incidence of flat feet in Medical Faculty of UPN Veteran Jakarta students in the 2019/2020 academic year (p = 0.001).